One- and 2-year outcomes of lumbar facet arthroplasty versus spinal fusion in young (<65 years) and old (≥65 years) patients for the treatment of degenerative spondylolisthesis and stenosis - Annabelle Shaffer, MS; Alexander K. Yu, MD; Albert Yu, PhD; Graham Huesmann, MD PhD; Ravishanker Iyer, PhD; Paul M. Arnold, MD (North American Spine Society Journal, 2024)
ABSTRACT: Background: Facet arthroplasty, an alternative to lumbar fusion, offers stabilization and preserves range of motion. This subanalysis of the TOPS IDE trial (FDA #G160168) compared facet arthroplasty, using the TOPS device, with a standard single-level transforaminal lumbar interbody fusion (TLIF) in patients stratified by age (<65 and ≥65 years) with symptomatic grade 1 degenerative spondylolisthesis with moderate to severe spinal stenosis at L2-5. Methods: Patient-reported outcomes (PROMS), including Oswestry disability index (ODI), visual analog pain scales (VAS), and Zurich claudication questionnaires (ZCQ), were assessed at baseline and multiple postoperative timepoints. Radiographic evaluation of flexion/extension range of motion (ROM) occurred at baseline, 12 months, and 24 months. Data were analyzed following an intention-to-treat model. Significance was defined as p<.05. Results: About 299 patients were included (TOPS=206, TLIF=93). The groups were similar at baseline. At 2 years, the TOPS group had a greater proportion of patients report ≥15-point improvement for ODI (93.8% versus 77.1%, p=.011) and ≥20-point improvement for VAS back (84.4% versus 61.8%, p=.014). At 1 year, TOPS group had a greater proportion of patients report clinically significant improvements in all ZCQ categories (91.6% versus 78.5%, p=.012). In patients <65 years, the TOPS group had improved PROMS compared to TLIF at 2 years; however, these differences were less pronounced in patients ≥65 years old. The TOPS groups preserved more ROM at 12 (2.8° 95%CI [1.87; 3.74], p<.0001) and 24 (2.99° 95%CI [1.82; 4.15], p<.0001) months compared to TLIF. ROM was similarly preserved in patients aged <65 and ≥65. The rate of adverse events did not differ significantly between treatment groups. Conclusions: Facet arthroplasty preserves more ROM in all ages and leads to improved PROMS compared to TLIF, particularly in younger patients.